(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Percutaneous endoscopic gastrostomy (PEG) is widely used for long-term enteral feeding. Peristomal infection and gastrointestinal leakage are recognised complications, whereas deep abdominal wall extension with persistent leakage is uncommon. Case presentation: A 72-year-old man with type 2 diabetes mellitus, sequelae after cardiac arrest, tracheostomy, and PEG feeding for more than 3 years developed fever, impaired consciousness, profuse peristomal gastric leakage, and extensive anterior abdominal wall inflammation 3 days after routine PEG tube replacement. On admission, findings were consistent with severe infection, hyperosmolar hyperglycaemic state, and acute kidney injury. Intervention and outcomes: Management included intensive resuscitation, broad-spectrum antibiotics, PEG tube removal, gastric decompression, jejunal tube placement for enteral feeding, and negative pressure wound therapy. Leakage progressively decreased, granulation tissue developed satisfactorily, and complete wound healing was achieved after 58 days. Conclusion: In severe peristomal PEG infection with persistent gastrointestinal leakage, a combined approach incorporating infection control, source control, maintenance of enteral nutrition, and negative pressure wound therapy may result in favourable outcomes. Early recognition and close local monitoring remain essential.